THEOLOGICAL ANALYSIS OF THE SYROMALABAR RESTORED ADULT BAPTISM (INITIATION) - Moolan, John (Asian Horizons, 2019)
Imitating the early practice,1 the Syro-Malabar Church for the first time has introduced adult initiation in 2005.2 The four stages within the proposed intervals of months, years, or different liturgical seasons resemble 2/3/4 years of early catechumenism.3 To make the children of God perfect, the Church has always maintained the unity of the sacraments of initiation as the gateway/door to the Church (AG, 7). Baptism with new birth, chrismation with new strength, and Eucharist with new nourishment equip to run a good run to attain the awaiting heavenly crown of justice (2 Tm 4:7-8).